Fungal Microbiota Profile in Newly Diagnosed Treatment-naïve Children with Crohn’s Disease - Mohammad El Mouzan; Feng Wang; Mohammad Al Mofarreh; Rajita Menon; Ahmad Al Barrag; Kirill S. Korolev; Ahmad A Al Sarkhy; Mona Al Asmi; Yassin M Hamed; Anjum Saeed; Scot E. Dowd; Asaad Assiri; et al. (2016)
Although increasing evidence suggests a role for fungi in inflammatory bowel disease [IBD], data are scarce and mostly from adults. Our aim was to define the characteristics of fungal microbiota in newly diagnosed treatment-naïve children with Crohn's disease [CD].The children referred for colonoscopy were prospectively enrolled in the study at King Khalid University Hospital, King Saud University, and Al Mofarreh Polyclinics in Riyadh. Tissue and stool samples were collected and frozen till sequencing analysis. The children with confirmed CD diagnosis were designated as cases and the others as non- IBD controls; 78 samples were collected from 35 children [15 CD and 20 controls]. Statistical analysis was performed to investigate CD associations and diversity.CD-associated fungi varied with the level of phylogenetic tree. There was no significant difference in abundance between normal and inflamed mucosa. Significantly abundant CD-associated taxa included Psathyrellaceae [p = 0.01], Cortinariaceae [p = 0.04], Psathyrella [p = 0.003], and Gymnopilus [p = 0.03]. Monilinia was significantly depleted [p = 0.03], whereas other depleted taxa, although not statistically significant, included Leotiomycetes [p = 0.06], Helotiales [p = 0.08], and Sclerotiniaceae [p = 0.07]. There was no significant difference in fungal diversity between CD and controls.We report highly significant fungal dysbiosis in newly diagnosed treatment-naïve CD children. Depleted and more abundant taxa suggest anti-inflammatory and pro-inflamatory potentials, respectively. Further studies with larger sample size and including functional analysis are needed to clarify the significance of the fungal community in the pathogenesis of CD.